Vulnerable security problems in learning management system (LMS) moodle - Vahe A. Arakelyan (Изд-во НАН РА)
In this paper the security mechanisms of LMS Moodle are investigated.Some vulnerable parts have been discovered and some solutions and methods are proposed to make the system more secure and safe.
Keywords: Mathematics; Computer software